Soekarno-Hatta in the Conflict of Indonesian Political Policies 1945-1956 - Minarwati, Elly; Siregar, Isrina (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Soekarno-Hatta was a proclaimer figure who had an important role in the struggle for Indonesian independence. In national and state life, the two figures were involved in conflicting opinions. After the Vice Presidential Decree No. Differences in cultural background, education and environment when born are also factors in the emergence of conflict. The aim of this research is to understand Indonesian political policy from 1945-1956, the beginning of political policy conflict between Soekarno and Hatta, and the impact of conflicting political policy on the Indonesian government system. This research uses historical methods consisting of heuristics, source criticism, interpretation, and historiography. The results of this research show that after Indonesia's independence, Indonesia's political identity had not yet been formed, but after the PPKI session, Indonesia's political identity began to form, Indonesia's post-independence political policy was more directed towards diplomacy, followed by the emergence of political parties and a change in the system from presidential democracy to parliamentary democracy. Soekarno-Hatta began to engage in polemics in 1932-1933, then during the colonial period the two figures clashed regarding tactics and strategy of struggle.